Population and future of sub-Saharan Africa - (:unkn) unknown (My University, 2002)
[To specify the singularity of this sub-continent of sub-Saharan Africa, it is first necessary to consider its historical origins and why it deserves to be considered separately from northern Africa. Then present its general demographic traits, and finally its problems in the twenty-first century.]
Keywords: African Research